Digital Simulation Test Method for Multiple Scenarios Relay Protection - Qingquan LIU; Peng YANG; Tiecheng LI; Xianzhi WANG; Minghao WEN (Zhongguo dianli)
The massive access of new energy has brought adaptability problems to relay protection. This paper proposes a digital simulation testing method for relay protection in multiple scenarios which can provide effective technical support for the performance evaluation of relay protection. From the perspective of the time sequence cooperation logic of relay protection devices, the cooperation relationship between protection devices, and the dimension of multi-scenario testing, this paper proposes the design and simulation method of relay protection simulation modules. The proposed method can meet the simulation requirements of various relay protection, and has passed the simulation test.